Intercultural communication in contexts - Martin, Judith N.; Nakayama, Thomas K. (McGraw Hill LLC, 2022)
"To reflect the increasing doubts about the benefits of globalization and increasing rise of populism both in the U. S. and abroad, we continue to emphasize the importance of these issues to intercultural communication"--Provided by publisher.